1932 թ. Ազգային-եկեղեցական ժողովը Ամենայն Հայոց եւ Մեծի Տանն Կիլիկիոյ կաթողիկոսութիւնների յարաբերութիւնների համապատկերում - Յովհաննիսեան, Էդգար (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
На протяжении всей истории Армянской Церкви отношения между Первопрестольным Эчмиадзином и Киликийским католикосатом были непростыми, временами даже крайне напряжёнными. 1920-е годы стали переломными в отношениях между двумя престолами. Исход армян из Киликии в 1921 году, изгнание Киликийского католикосата, а также установление советской власти в Армении существенно повлияли на их дальнейшее развитие. После смерти Католикоса Всех Армян Геворга V Суренянца в 1930 году предполагалось созвать Национально-церковное собрание для избрания его преемника. Эти выборы стали бы первыми после установления советской власти в Армении. Однако собрание состоялось лишь в 1932 году, и его итогом стало избрание Католикосом Хорена I Мурадбекяна. Впервые для участия в этих выборах были приглашены Католикос Вели- кого Дома Киликийского Саак II Хабаян и его коадъютор, Католикос Бабкен I Кюлесерян, а также духовные и светские представители пяти епархий Киликийского католикосата. Хотя последние по разным причинам не смогли принять участие в выборах, сам факт их приглашения ознаменовал новый этап в отношениях между двумя престолами. В статье анализируются выборы Католикоса 1932 года в контексте отношений между Первопрестольным Эчмиадзином и Киликийским католикосатом. Throughout the history of the Armenian Church, the relations between the Mother See and the Catholicosate of Cilicia have not always been smooth. At times, these relations have been extremely tense. Significant changes occurred in the relations between the two sees in the 1920s. The exodus of Armenians from Cilicia in 1921 and the expulsion of the Catholicosate of Cilicia, as well as the establishment of Soviet rule in Armenia, had a profound impact on the relations between the two Catholicosates. In 1930, following the death of Catholicos of All Armenians Gevorg V Surenyants, a National-Ecclesiastical Assembly was envisaged to elect a new Catholicos. These elections were to be the first after the establishment of Soviet rule in Armenia. However, the assembly was convened only in 1932, resulting in the election of Khoren I Muradbekyan as the new Catholicos. For the first time, Catholicos of the Great House of Cilicia Sahak II Khapayan and his coadjutor Catholicos Babken I Kyuleseryan, as well as spiritual and secular representatives of the five dioceses of the Catholicosate of Cilicia, were invited to participate in these elections. Although they were unable to attend for various reasons, their invitation marked a new phase in the relations between the two Sees. The article analyzes the 1932 Catholicosate elections in the context of relations between the Mother See and the Catholicosate of Cilicia.
Keywords: Հայոց եկեղեցւոյ պատմութիւն